Transitional Dynamics in a Growth Model with Distributive Politics - Chetan Ghate (Max Planck Institute of Economics, 2006)
This paper constructs a dynamic analysis of the growth and distribution models of Das and Ghate (2004) and Alesina and Rodrik (1994) when leisure is valued by agents. When leisure enters the utility function, we show that the tax rate on capital income chosen in a political equilibrium is lower than the growth maximizing tax rate. This slows growth down, but for a very different reason than in Alesina and Rodrik (1994). Here, unanimity holds, and slower growth comes together with valued leisure, while in AR, slower growth comes from conflicting choices over the tax rate, with a capital poor median voter prevailing. Our results generalize the work of Alesina and Rodrik (1994) and Das and Ghate (2004) in two ways. First, we assess the impact of redistributive politics on growth by looking at the effect of income inequality on the tax rate and labor supply. Second, using the set up of Das and Ghate (2004), we provide a dynamic analysis of Alesina and Rodrik (1994) where majority voting determines the extent of distribution, and thus, a relationship between inequality and growth. The general insight gained from the analysis is that characterizing the transitional dynamics in a model of redistributive politics and growth with endogenous leisure is not intractable.
Keywords: E62; O40; P16; 330; Distributive Conflict; Endogenous Distribution; Median Voter Theorem; Endogenous Growth; Positive Political Economy